Hair cortisol and changes in cortisol dynamics in chronic kidney disease - Boswell, Laura; Vega-Beyhart, Arturo; Blasco, Miquel; Quintana, Luis F.; Rodríguez, Gabriela; Díaz-Catalán, Daniela; Vilardell, Carme; Claro, María; Mora, Mireia; Amor, Antonio J.; Casals, Gregori; Hanzu, Felicia A. (Frontiers in Endocrinology, 2024)
Objective: We compared hair cortisol (HC) with classic tests of the hypothalamic-pituitary-adrenal (HPA) axis in chronic kidney disease (CKD) and assessed its association with kidney and cardiometabolic status.A cross-sectional study of 48 patients with CKD stages I-IV, matched by age, sex and BMI with 24 healthy controls (CTR) was performed. Metabolic comorbidities, body composition and HPA axis function were studied.Results: Seventy-two subjects (age 52.9±12.2 years, 50%women, BMI 26.2±4.1kg/m 2 ) were included.Metabolic syndrome features (hypertension, dyslipidaemia, glucose, HOMA-IR, triglycerides, waist circumference) and 24h-urinary proteins increased progressively with worsening kidney function (p<0.05 for all). Reduced cortisol suppression after 1-mg-dexamethasone-suppression (DST) (p<0.001), a higher noon (12:00h pm) salivary-cortisol (p=0.042) and salivary cortisol AUC (p=0.008) were seen in CKD. 24h-urinary-free-cortisol (24h-UFC) decreased in CKD stages III-IV compared to I-II (p<0.001); higher midnight-salivary-cortisol (p=0.015) and lower suppressibility after 1-mg-DST were observed with declining kidney function (p<0.001). Cortisol-after-DST cortisol was >2mcg/dL in 23% of CKD patients (12.5% in stage-III and 56.3% in stage-IV); 45% of them had cortisol >2mcg/dL after low-dose 2-day-DST, all in stage-IV (p<0.001 for all). Cortisol-after-DST was lineally inversely correlated with eGFR (p<0.001). Cortisol-after-DST (OR 14.9, 95%CI 1.7-103, p=0.015) and glucose (OR 1.3, 95%CI 1.1-1.5, p=0.003) were independently associated with eGFR <30ml/min/m 2 . HC was independently correlated with visceral adipose tissue (VAT) (p=0.016). Cortisol-after-DST (p=0.032) and VAT (p<0.001) were independently correlated to BMI.: Cortisol-after-DST and salivary cortisol rhythm present progressive alterations in CKD patients. Changes in cortisol excretion and HPA dynamics in CKD are not accompanied by significant changes in long-term exposure to cortisol evaluated by HC. The clinical significance and pathophysiological mechanisms explaining the associations between HPA parameters, body composition and kidney damage warrant further study.